COMPOUND CONTENT OF LOCAL CURCUMIN (CURCUMA XANTHORRHIZA) IN NORTH SULAWESI, INDONESIA - Demmassabu, Langimanapa Sofia; Paat, Frangky Jessy; Turang, Deflly Ansye Shilfana; Tumbelaka, Selvie; Mamuaja, Christine F; Wantasen, Sofia; Toding, Marjam M.; Pongoh, Jantje; Paulus, Jeanne Martje (ITScience (Information Technology and Science), 2023)
This Zingiberaceae plant is widely used as medicine, including temulawak. Because curcuma (C.xanthorrhiza) is a medicinal plant that has many benefits and includes plants needed in large quantities compared to other medicinal plants. Traditionally rhizomes Temulawak is used to treat stomach ailments, liver disorders, constipation, diarrhea, dysentery, fever, hemorrhoids, hypotriglyceridaemic, and anti-inflammatory. Study about plant Curcuma local ignite still not enough researched so that not yet get information compounds which contained in the local curcuma of North Sulawesi for the development for biopharmaceutical development, mapping in the distribution of plants, ecology, plant conservation and protection to maintain local wisdom. Histochemical Test is a method to determine the content of chemical compounds in a plant tissue qualitative. Testing can be done by adding a special reagent or solution to the incision organ plant and will give color which Specific. Activity study this will test curcumin compound group on local ginger from North Sulawesi by histochemical method. research that done is study non experiment with design descriptive qualitative. The results showed that North Sulawesi local white temulawak powder contained curcumin in a sample with a sample weight of 0.10 g at a sample spotting volume of 20 µl with a sample spotting volume of 2040 nanograms, curcumin levels were <0.10 nanograms/mg. Curcumin biosynthesis is influenced by site conditions, agro-climate, genotype, and plant cultivation.